The Influence of Work-Life Balance and Work Engagement on Organizational Citizenship Behavior Mediated by Self-Efficacy at PT. LG Electronics Indonesia - Amalia, Fitria Fatihah; Setyaningrum, Retno Purwani (BASKARA : Journal of Business and Entrepreneurship, 2024)
Every company needs quality human resources, innovation and creativity so that a company can continue to compete with other companies so that employee performance is really needed by companies to improve company performance and employee performance. This research aims to determine the influence of the Work Life-Balance variable and the Work Engagement variable on Organization Citizenship Behavior mediated by the Self-Efficacy variable in employees PT. LG Electronics Indonesia. The research method used is a quantitative method with the research population namely employees of PT. LG Electronics Indonesia and the sample size was 87 people. The analytical method used in this research is Partial Least Square (PLS) using the SmartPLS version 3.0 program. Based on this research, that Work-Life Balance has no significant influence on Organization Citizenship Behavior with a t-statitic value (1,566 1,96), Work Engagement has a significant influence on Organization Citizenship Behavior with a t-statitic value (3,166 1,96), Self-Efficacy has a significant influence on Organization Citizenship Behavior with a t-statitic value (2,056 1,96), Work-Life Balance has a significant influence on Self-Efficacy with a t-statitic value (4,211 1,96), Work Engagement has a significant influence on Self-Efficacy with a t-statitic value (5,495 1,96), Work-Life Balance mediated by Self-Efficacy does not have a significant influence on Organization Citizenship Behavior with a t-statitic value (1,877 1,96), Work Engagement mediated by Self-Efficacy does not have a significant influence on Organization Citizenship Behavior with a t-statitic value ( 1,811 1,96).